Reflections on health promotion fieldwork in Nepal: Trials and tribulations - Mahato, Preeti; Tamang, Pasang; Simkhada, Bibha; Wasti, Sharada P.; Devkota, Bhimsen; Simkhada, Padam; Teijlingen, Edwin R. van (Journal of Health Promotion, 2022)
Fieldwork is often a crucial part of community-based public health studies. However, few researchers write about this, often challenging, process. This paper highlights various occasions where fieldwork in the area of public health, health promotion or community health was more difficult than expected or did not go as planned. Our reflections on working in the field will help less experienced health researchers, or those new to conducting research in Nepal, in their research development. Moreover, this paper is also calling upon health promotion researchers to share more details about the process of doing fieldwork and its trials and tribulations. Our key advice is to be inquisitive and openminded around fieldwork, followed by: be prepared for your fieldwork, conduct a risk assessment of what might go wrong and consider your options to overcome such trials and tribulations. Fieldwork is unpredictable; therefore, it is important to share practical lessons from the field which helps other to better understand these tribulations, and learn from them. Moreover, sharing such information may guide new researchers and help them identify strategies that can address those issues and challenges in their future health promotion studies.